Market timing of long-term debt issuance - Jonathan Witmer (Bank of Canada, 2009)
The literature on market timing of long-term debt issuance yields mixed evidence that managers can successfully time their debt-maturity issuance. The early results that are indicative of debt-maturity timing are not robust to accounting for structural breaks or to other measures of debt maturity from firm-level data that account for call and put provisions in debt contracts. The author applies the analysis from some recent U.S. studies to aggregate Canadian data to determine whether the market-timing results are robust. Although the relation between debt maturity and future excess returns is in the same direction as in the United States, it is not statistically significant. This mixed evidence, combined with the difficulties in interpreting predictive regressions of this nature, provides little support for the notion that firms can effectively reduce their cost of capital by varying the maturity of their debt issuance to take advantage of market conditions. Managers do, however, try to time their debt-maturity issuance, given that long-term corporate debt issuance in both Canada and the United States is negatively related to the term spread.
Keywords: G30; G38; 330; Financial markets; International topics; Finanzmarkt; Unternehmensfinanzierung; Schulden; Laufzeit; Kapitalkosten; Zinsstruktur; USA; Kanada